Influence of some anthropometric, motor and bone mass parameters on short distance running - Ramadani, L.; Rashiti, N.; Bekolli, L.; Heta, G. (Journal of Education, Health and Sport, 2021)
The knowledge on morphological development and their impact on motor skills in short distance athletes should be one of the main preoccupations of athletics coaches, because any scientific research in the field of physical culture and sports is concerned with proving the development and evaluation of anthropological characteristics which are responsible in achieving success in athletics.The purpose of this paper is to prove the impact of some anthropometric, motor-specific characteristics and those of bone weight in short distance running, specifically in 100 meters, with students aged 19 ± 6 years, of the Faculty of Physical Education and Sports in Pristina.The sample of this research included a total of 75 students aged 19 of the Faculty of Physical Education and Sports in Pristina.The variables which were applied in this research were 7 anthropometric variables and 6 motor variables and 1 specific motor variable.Regression analysis in the manifest space was applied to determine the relationship between predictive variables (anthropometric and motor characteristics) and criterion variable (100 m running).